2004
DOI: 10.1111/j.0042-9007.2004.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐transmitted bacterial infection: risks, sources and interventions

Abstract: Records of the transmission of bacterial infections by transfusion date back to the beginning of organized blood banking. Despite tremendous strides in preventing viral infection through careful donor screening and viral testing, there has been little improvement in reducing the risk of bacterial sepsis since the introduction of closed collection systems. Based on the French Haemovigilance study, the British Serious Hazards of Transmission (SHOT) study and fatality reports to the United States Food and Drug Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 51 publications
3
51
0
Order By: Relevance
“…This emergence of this pattern from SHOT reporting led to the recommendation that strategies be developed to reduce this. Similar observations were made in France and elsewhere (Wagner, 2004). The Blood Services introduced diversion of the first 20 ml of each donation in 2002, and also methods to improve skin cleansing, which have to be meticulously performed.…”
Section: Reduction Of Unpredictable Transfusion Reactionssupporting
confidence: 89%
“…This emergence of this pattern from SHOT reporting led to the recommendation that strategies be developed to reduce this. Similar observations were made in France and elsewhere (Wagner, 2004). The Blood Services introduced diversion of the first 20 ml of each donation in 2002, and also methods to improve skin cleansing, which have to be meticulously performed.…”
Section: Reduction Of Unpredictable Transfusion Reactionssupporting
confidence: 89%
“…As a result, the most predominant bacteria isolated are usually commensals of the skin or gastrointestinal tract flora. A report from the American Red Cross on detection of bacterial contamina- tion in platelets showed that the majority of isolates were Gram-positive aerobic pathogens (nearly 75%), in line with the organisms identified in platelet units implicated in cases of transfusion-associated sepsis (56% Gram-positive aerobes) [7].…”
Section: Bacterial Infectionsmentioning
confidence: 61%
“…The risk of bacterial infection has emerged as the major cause of transfusion related morbidity and mortality, in part due to the reduction of other risks [4,[7][8][9][10]. Bacterial contamination is more frequent in platelet concentrates (PLT) than in red blood components most likely because many microorganisms can survive and propagate under the storage conditions typically used for PLT (20-24°C), but less so for RBC (1-6°C) [8][9][10][11] As a consequence of the increasing awareness and clinical relevance of bacterial contamination of blood components, the AABB (formerly The American Association of Blood Banks) released standards to diminish bacterial TTI [12] in 2004.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…In contrast, despite bacterial screening testing, the American Red Cross (ARC) published TTBI frequencies between 1:40,000 and 1:193,000 depending on the collecting procedure. The fatality rate was one in 500,000 platelet units [10]. Swissmedic described an estimated TTBI risk of 1:600,000 donations for the last decade [2]; after the introduction of pathogen inactivation procedure for all PC (2011), no further TTBI was confirmed [11].…”
Section: Discussionmentioning
confidence: 99%